Noninvasive Assessment of Arterial Stiffness and Risk of Coronary Artery Disease - Rahman, Md Mustafizur; Siddique, Md Abu; Banerjee, Sajal Krishna; Ahmed, Chaudhury Meshkat; Ahmed, Md Khurshed; Rahman, Md Mukhlesur; Ahmed, Md Iftekhar; Sultan, Md Ashraf Uddin; Hossain, Ahmed Shafikul (University Heart Journal, 2012)
The early prediction of Coronary artery disease (CAD) is a major goal of healthcare through out the world. Aortic stiffness reflecting impaired elasticity of the aorta is shown to be an independent predictor of coronary artery disease which can be measured noninvasively. The aim of the study was to establish the noninvasive markers of Aortic stiffness as the predictor of CAD. In this prospective, observational study, total 100 patients were examined who were clinically suspected of having CAD and were scheduled to undergo CAG. Then the markers of aortic stiffness like Aortic strain, aortic distensibility and aortic propagation velocity were measured by transthoracic echocardiography. Other markers of aortic stiffness like Male sex, aging, systolic blood pressure and pulse pressure were significantly higher in the CAD group. Here it is showed that CAD can be significantly determined by aortic propagation velocity (AVP) cut off value d41cm/sec. 82% patients were found CAD by AVP who had truly CAD on the basis of CAG and 96% patients were found no CAD by AVP who had no CAD by CAG. Thus an AVP value < 41 cm/sec predicted CAD with 82% sensitivity, 96% specificity (positive predictive value 95.35%, negative predictive value 84.21% and accuracy were 89%). In conclusion, bedside risk stratification of CAD is feasible by echcardiographic determination of Aortic propagation velocity(AVP). DOI: http://dx.doi.org/10.3329/uhj.v7i2.10838 University Heart. Journal Vol. 7, No. 2, July 2011